Scholingsaktiviteiten in het kader van de herstructurering in Limburg - J. Loos, (Netherlands Journal of Geosciences, 1971)
Due to the closing of the coal mines a significant source of employment is disappearing. Many of the skilled professionals of the mining industry are, from the point of view of education, training and aquired skills, unit for the types of alternative employment that is being offered. Training of various types, from adding to a man's skills to complete retraining is needed and forms the subject of this paper. One of the types of training is provided by the centres of professional training for adults, another and by far the most important is the reschooling by the employers or by special job training centres, following the guidelines as laid down by the Directory General of the provincial employment office. Certain aspects of reschooling are already covered by other authors in this booklet. The favourable results obtained in the retraining and reschooling programs of the ex-miners is for a large measure due to the excellent co-operation between the provincial employment authorities, industry, the labour unions and the European Coal and Steel Community.